2001
DOI: 10.1111/1464-0597.00063
|View full text |Cite
|
Sign up to set email alerts
|

Commentaries

Abstract: Commentaries by: Alexandra M. Freund and Michaela Riediger, What I Have and What I Do— The Role of Resource Loss and Gain Throughout Life, p.370 Richard S. Lazarus, Conservation of Resources Theory (COR): Little More Than Words Masquerading as a New Theory, p.381 James Campbell Quick and Joanne H. Gavin, Four Perspectives on Conservation of Resources Theory: A Commentary, p.392 Ralf Schwarzer, Stress, Resources, and Proactive Coping, p.400 Murray S. Thompson, A Rose By Any Other Name . . . : A Commentary onHob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 55 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…Younger adults might be less willing to spend resources such as money on anything but themselves because they need these resources to achieve important developmental goals. Taking an evolutionary perspective, Freund and Riediger (2001) argued that the accumulation and display of resources is particularly important in young adulthood. First, young adults typically have not yet had the same amount of time and number of opportunities to acquire and accumulate resources as middle-aged or older adults have.…”
Section: Age and Altruismmentioning
confidence: 99%
See 1 more Smart Citation
“…Younger adults might be less willing to spend resources such as money on anything but themselves because they need these resources to achieve important developmental goals. Taking an evolutionary perspective, Freund and Riediger (2001) argued that the accumulation and display of resources is particularly important in young adulthood. First, young adults typically have not yet had the same amount of time and number of opportunities to acquire and accumulate resources as middle-aged or older adults have.…”
Section: Age and Altruismmentioning
confidence: 99%
“…Based on the hypothesis that altruism-in the sense of a willingness to contribute to the public good, such as the environment or charitable donations-increases with age, these studies investigate adult age-related differences in self-reported and behavioral altruism. As will be elaborated in more detail below, this hypothesis is based on the assumption that maximizing one's own resources becomes less important with increasing age (Freund & Riediger, 2001), and that the shorter future time perspective associated with older adulthood activates altruistic values (see also Brandtstädter, Rothermund, Kranz, & Kühn, 2010;Ritter & Freund, in press). …”
mentioning
confidence: 99%
“…Moreover, developmental tasks in young adulthood are primarily geared toward gains (e.g., attaining an education, getting a job, founding a family), whereas those in older adulthood reflect primarily the avoidance of losses (e.g., maintaining health-related and cognitive functioning in the face of age-related decline; Freund & Ebner, 2005). In the developmental phase of younger adulthood, then, attaining gains seems of primary importance in order to achieve developmental tasks and accumulate resources that are important for further development (Freund & Riediger, 2001). In contrast, the maintenance of functioning and avoidance of losses should become more important in older adulthood when losses in resources threaten functioning (Freund & Ebner, 2005).…”
Section: Motivational Changes Across Adulthoodmentioning
confidence: 99%
“…In this way, accumulated resources may be seen as a safeguard against the potential loss from future stressors. Resource accumulation reflects future-oriented thinking and a proactive approach to coping with future events (Aspinwall, 2005;Schwarzer, 2001). Resource surpluses thus should be associated with more positive outcomes (Hobfoll, 1989).…”
Section: Conceptual Frameworkmentioning
confidence: 99%